Receptor-specific adhesion and clinical disease in Plasmodium falciparum. - Newbold, C; Warn, P; Black, G; Berendt, A; Craig, A; Snow, B; Msobo, M; Peshu, N; Marsh, K (1997)
One important factor in the virulence of infections with Plasmodium falciparum is the adherence of infected erythrocytes to small vessel endothelium. In infections that lead to serious, life-threatening disease accumulation of large numbers of infected cells in particular organs is thought to lead to organ dysfunction or failure. This is of particular relevance when the affected organ is the brain, leading to the development of cerebral malaria. Many different endothelial receptors for infected red blood cells have been identified. Some receptors such as CD36 and thrombospondin are used by all parasite isolates, whereas others such as intercellular adhesion molecule-1 (ICAM-1) or vascular cell adhesion molecule (VCAM) are used by a subset of field and laboratory isolates. While it has been speculated that the ability to bind or affinity of binding to a particular endothelial receptor may be related to the pattern of disease, only studies with limited numbers of patients have been carried out to date and these have been in general inconclusive. Here we have taken parasite isolates from 150 patients with defined clinical syndromes as well as isolates from 50 healthy but parasitized community controls and quantitatively assessed their binding to purified endothelial receptors in vitro. Our results show that disregarding the level of adhesion, all parasites bind to CD36, most bind to ICAM-1, few bind to VCAM, and almost none bind to E-selectin. In assessing the degree of binding we show that 1) binding to all receptors was reduced in parasites taken from severely anemic patients; 2) binding to CD36 is identical in parasites from cerebral malaria patients and community controls but slightly elevated in parasites from nonsevere cases; and 3) binding to ICAM-1 is highest in cerebral malaria patients. Because rosette formation by uninfected cells has also been a phenotype associated with disease severity and one that may interfere in vitro with receptor binding, we also assessed rosette formation in all isolates. In this study the highest level of rosette-forming parasites was found in the anemic group and not the cerebral malaria group. Stratifying the data for the frequency of rosette formation showed that the above results were not significantly altered by this phenomenon. Our data are not consistent with a role for binding to CD36 in the development of severe disease but show an association between the degree of binding to ICAM-1 and clinical illness in nonanemic patients.